2014
DOI: 10.1371/journal.pone.0095428
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Transcriptome and Small RNA Analyses of Two Amorphophallus Species

Abstract: Konjac is one of the most important glucomannan crops worldwide. The breeding and genomic researches are largely limited by the genetic basis of Amorphophallus. In this study, the transcriptomes of A. konjac and A. bulbifer were constructed using a high-throughput Illumina sequencing platform. All 108,651 unigenes with average lengths of 430 nt in A. konjac and 119,678 unigenes with average lengths of 439 nt were generated from 54,986,020 reads and 52,334,098 reads after filtering and assembly, respectively. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 23 publications
0
23
1
Order By: Relevance
“…S4 C and E), indicating that this gene is not sufficient for HM production. Interestingly, no AtMSR1 homolog was identified in Ak transcriptome datasets (8,22). We thus evaluated the function of AtMSR1 in combination with the AkCSLA3 enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…S4 C and E), indicating that this gene is not sufficient for HM production. Interestingly, no AtMSR1 homolog was identified in Ak transcriptome datasets (8,22). We thus evaluated the function of AtMSR1 in combination with the AkCSLA3 enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…The galactomannans are known to be present at high levels within the endosperm of clusterbean seeds. To date, miRNA‐based regulation of glucomannan/galactomannan is reported only in Amorphophallus (Araceae) especially in leaves (Diao et al ., ). Hence, our present investigation targets at generating knowledge about miRNA regulatory gene networks and metabolic processes that may influence galactomannan content of cultivated genotypes of C. tetragonoloba .…”
Section: Discussionmentioning
confidence: 97%
“…Seven enzymes, namely sucrose synthase (SuS), phosphoglucose isomerase (PGI), phosphoglucomutase (PGM), phosphomannose isomerase (PMI), phosphomannomutase (PMM), starch synthase (SS) and UDP‐Glc/UDP‐Gal 4‐epimerase (UGE), were found in the clusterbean unigene data sets. Experimental evidence has also shown that these enzymes exhibit corresponding catalytic functions (Diao et al ., ). Thus, the combinatorial analysis of small RNA and transcriptome data has the potential to identify regulatory miRNAs involved in biosynthetic pathway of galactomannan and the corresponding mRNA targets.…”
Section: Discussionmentioning
confidence: 97%
“…This strategy can enrich the large amounts of expressed sequence data for non-model organisms for which the reference genome or transcriptome is not available (Martin & Wang, 2011). Several non-model organisms in the Araceae family, including Z. aethiopica (Cândido et al, 2014) Arum concinnatum (Onda et al, 2015), Anthurium andraeanum (Tian et al, 2013; Yang et al, 2015; Li et al, 2015), Pinellia ternate (Wang et al, 2014), Amorphophallus konjac and A. bulbifer (Zheng et al, 2013; Diao et al, 2014), have been recently studied by transcriptome sequencing, which has provided a better understanding of these crops. EST-SSR markers have been successfully characterized and developed in P. ternate (Wang et al, 2014), A. konjac and A. bulbifer (Zheng et al, 2013).…”
Section: Introductionmentioning
confidence: 99%